EFEKTIVITAS PENDEKATAN MINDFULLNESS UNTUK MENINGKATKAN RESILIENSI AKADEMIK SISWA SEKOLAH MENENGAH ATAS: LITERATURE REVIEW - Lani Cahyani; Eka Wahyuni (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to analyze the effectiveness of mindfulness approaches to increase the academic resilience of high school students. This article reports on the results of a review of articles published from 2015 to 2023 that specifically examine mindfulness approaches to improve students' academic resilience. Researchers used international databases, such as journal.sagepub, reseachgate, libgen, willey and springer as well as the national data force, SINTA. The results of an analysis of several journal articles and finally selected 11 articles stating that mindfulness approaches are effective for increasing students' academic resilience. This empirical evidence provides a basis for researchers to find out how mindfulness approaches can increase students' academic resilience. Students who have high academic resilience are able to change new perceptions for their situation, remain optimistic and creative thinking and positive feelings so that they can get through difficult conditions. By attending mindfulness training, students become fully aware and remain focused on achieving success under academic pressure.